ANALISIS SPASIAL KEJADIAN PENYAKIT TUBERKULOSIS PARU BERHUBUNGAN DENGAN FAKTOR RISIKO KONDISI RUMAH DAN LINGKUNGAN DI KOTA PALEMBANG - , Budi Santoso, Dr. Iswanto, SpP, FCCP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Program control tuberculosis (TB) expects to find 70% of the estimated presence of new acid-resistant patients positive and then cure 85% of these patients and maintain it. Thus the expected prevalence rates and deaths from tuberculosis will decline by 50% in 2015 compared to 1990. That means the achievement of Millennium Development Goals (MDG's). Palembang City Health Office in its report says the percentage of healthy housing conditions in the city of Palembang as much as 76.62% of the 207,618 homes inspected. Total number of houses as many as 257,130 homes. Methods: This study uses a case-control method. Cases are smear positive TB patients registered in the TB form 03 Palembang. Controls are the people who do not suffer from tuberculosis who visited the health center. Number of samples: 346 respondents, consisting of 173 cases and 173 controls. Research using several tools, namely: observation sheet (form), questionnaires and GPS. Data analysis techniques using three approaches, namely the individual analysis, spatial analysis by looking at the spread of tuberculosis and its relation to population density and the density of homes, the third, is a descriptive analysis of the level of ease of implementation units health coverage and the proximity of houses to a river. Results: Variables associated with smear positive pulmonary tuberculosis are variable density residential, room temperature, lighting, humidity and 10 Î¼ particullat matter (PM 10). The analysis showed the density of occupancy, lighting and PM 10 are statistically significant (p <0.05). The most powerful variable is the density residential with a value of .000 sig, Exp Î² = 2,603,95% confidence interval = 1,585-4,072. Spatial analysis indicate the presence of 1 (one) most Likely clusters, namely at the point of case 2 58 05.5 latitude and 104 47'43 .6 "BT, as far as a radius of 492.37 meters. The relationship between population density per km2 overlay showed no meaningful relationship. Density houses in the area showed a significant association with the number of smearpositive pulmonary TB cases (coefficient 0.0003